Factors influencing adaptation strategies by livestock owners to combat climate variability in Karnataka state: Application of ordered logistic regression model - PARAMESWARANAIK, J; KUMAR, R SENTHIL; BHAWAR, R S; DARSHAN, N P; PATEL, DIKSHA (The Indian Journal of Animal Sciences, 2016)
Climate variability refers to the way climate fluctuates yearly above or below a long-term average value. It is considered as one of the most serious long-term challenges faced by livestock rearers, in this context it is important to know about the adaptation strategies followed by the livestock rearers in combating the climate variability vagaries. The present study was conducted in purposively selected northern dry zone of Karnataka with 120 livestock rearers, the major findings of the study were: Majority of the respondents were following adaptation strategies like keeping, promoting and interested in local breeds (60.83%), about 42.50% of livestock rearers made changes in micro-climate in cattle shed/stall, and 47.50% of respondents were providing extra concentrate, minerals supplementation and feed additives to their livestock, etc. An ordered logit model is estimated to investigate the factors influencing adoption of various strategies to combat climate variability. Among the adaptation strategies, the proportional odds assumption was satisfied only for keeping, promoting and interest in local breeds; change in micro-climate in cattle shed /stall and shifting from large ruminants to small ruminants were found significant with the herd size; land holding and education level of the respondents and for other variables the ordinal regression was not performed. It was also found that livestock rearers followed the cost effective adaption strategies, and all the adaptation techniques were region-specific, requiring no external help and were inherently scientific.